Collaborative Governance sebagai Pengungkit Inovasi Smart City: : Analisis Transformasi Layanan Publik Digital di Indonesia - Zirly Arrayanal Bilqis; Gina Apriyanti; Tesa Andani; Ersa Muquaffa Syahrani (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
The transformation of smart cities in Indonesia indicates that the success of public service innovation is highly dependent on the quality of collaborative governance that connects the government, the private sector, academia, and civil society. This study aims to analyze the role of collaborative governance in promoting the effective implementation of smart cities through joint decision-making mechanisms, resource distribution, and trust-building among stakeholders. The research method used is a qualitative approach with a literature review, analyzing various relevant literature, policy documents, and previous research findings regarding the implementation of smart cities and collaborative governance in Indonesia. This approach allows the researcher to map various forms of collaboration, barriers, and factors affecting the effectiveness of collaborative governance in smart city innovation. The results of the study show that clear collaboration structures, facilitative leadership, and deliberative interactions enhance the responsiveness, transparency, and adaptability of digital public services. Various innovations, including data integration, command centers, public participation platforms, and smart mobility, demonstrate improved service quality when collaborative processes are consistently applied. However, challenges such as sectoral ego, disparities in human resource capacity, and infrastructure limitations still hinder optimal implementation. This study concludes that collaborative governance is a fundamental prerequisite for the sustainability of smart city innovation, and recommends strengthening regulations, increasing digital capacity, and designing more inclusive and institutionalized collaboration.